1994
DOI: 10.1152/ajpheart.1994.266.4.h1572
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia stimulates release of ANP and BNP from perfused rat ventricular myocardium

Abstract: We determined the effect of hypoxia on cellular energy state and ventricular atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP), and endothelin-1 (ET-1) release in an isolated perfused heart preparation after removal of all atrial tissue in 21- to 24-mo-old Wistar-Kyoto rats. After a control period (14 min), the ventricles (n = 6) were exposed to 30 min of hypoxia by changing the gas mixture to N2-CO2 (95:5 vol/vol; hypoxic period) and back to O2-CO2 (95:5 vol/vol) for 30 min (reoxygenation peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 0 publications
6
65
1
3
Order By: Relevance
“…In one study, increase in serum BNP levels during electrocardiographic exercise testing was found in patients with stable angina pectoris. Also, the rise in serum BNP levels was correlated with the size of the ischaemic myocardium, assessed with positron emission tomography 17. In patients with angiographically proven coronary artery disease, serum NT-proBNP levels were related to the extent and severity of coronary artery disease 18…”
Section: Discussionmentioning
confidence: 99%
“…In one study, increase in serum BNP levels during electrocardiographic exercise testing was found in patients with stable angina pectoris. Also, the rise in serum BNP levels was correlated with the size of the ischaemic myocardium, assessed with positron emission tomography 17. In patients with angiographically proven coronary artery disease, serum NT-proBNP levels were related to the extent and severity of coronary artery disease 18…”
Section: Discussionmentioning
confidence: 99%
“…Patients with unstable angina have been reported to exhibit elevated plasma BNP levels, 21,22) possibly due to ischemiainduced BNP production from the myocardium. 23) Although no subjects assigned to the coronary artery disease group in the present study showed clinically unstable angina, possible asymptomatic or subclinical myocardial ischemia due to exertion may increase myocardial BNP production and circulating levels. 8,23) Hence, a number of subjects with coronary artery disease were identified exclusively by BNP testing.…”
Section: Discussionmentioning
confidence: 58%
“…Thus a mechanism other than LV dysfunction might be responsible for the adverse outcome in patients with NSTEACS and high levels of NT-proBNP . Toth et al (25) have found evidence that tissue hypoxia alone triggers release of BNP in absence of LV dysfunction. These results were confirmed by a recent physiological study showing that ventricular BNP gene expression is up-regulated by myocardial hypoxia resulting in augmented plasma concentrations of BNP and NT-proBNP (26).…”
Section: Discussionmentioning
confidence: 99%